Studying and prevention of bullying in the school environment: results of a mini research (The Journal of Psychology and Sociology, 2020)
The article discusses the problem of studying and preventing bullying based on the analysis of for- eign and domestic programs about countering bullying in a school environment.The results of a mini-study dedicated to identifying bullying at school are presented.According to the results of the methods performed, some common features of children that are capable of falling into the risk group of bullying are noted: high level of anxiety, emotional lability, emo- tional volitional instability, shyness, low self-esteem, inadequate level of claims, lack of communication, low locus of control, tendency of being driven, avoidance - as the main strategy for overcoming conflict situations.Based on the diagnostic results, a “risk group” was identified - “potential bullying victims”, with which the emotional development program named “World of Emotions” and training on the formation of anti-bullying skills were conducted. The results of this work demonstrated positive dynamics, which confirmed the assumption that it is necessary for students to form skills to counter bullying - anti-bullying skills, which include: emotional stability, resilience, poise, willpower, mental strength, etc.As a result, it is noted that the silence, suppressed stress and impotence of teachers and psycholo- gists regarding bullying situations can be transformed into competent and open ways of responding, but for this it is necessary to work on the formation of a clear, coordinated and, worked out to the level of certain actions, position of school staff broadcasting the value of respectful relationships and the need to stop bullying.Key words: bullying, victimization, anti-bullying skills, potential victims of bullying, emotional labil- ity, emotional volitional instability, emotional stability, resilience, emotional strength.